Exploiting Popularity to Improve Blog Search - Santos, Luiz Guilherme P.; Gonçalves, Marcos André; Laender, Alberto H. F. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2010)
The blogosphere is a highly dynamic and interconnected subset of the Web that has triggered a lot of interest due to its social and personal nature. We present a study of an important social aspect of blogs, namely popularity. This study, based on the most popular blogs from four important blog domains in Brazil, shows that, popularity has been underexploited by at least the most popular search engines in the context of blog search. In our experiments, queries specifically formulated for retrieving these popular blogs were not capable of ranking them at the top positions (top 100) by the most popular search engines. We also provide evidence that explicitly incorporating popularity into the search engine algorithm has the potential to significantly improve the final rankings.